Magnesium for Treatment of Reversible Cerebral Vasoconstriction Syndrome: Case Series. (July 2016) - Mijalski, Christina; Dakay, Katarina; Miller-Patterson, Cameron; Saad, Ali; Silver, Brian; Khan, Muhib
We describe 2 cases of reversible cerebral vasoconstriction syndrome (RCVS) with refractory headache aborted by intravenous magnesium. Case 1 is a 53-year-old woman with subarachnoid hemorrhage due to RCVS presented with refractory headache and persistent vasospasm, despite aggressive treatment with calcium channel blockers (CCBs) and systemic corticosteroids. Subsequently, she experienced dramatic relief of symptoms with intravenous magnesium therapy. She continued oral maintenance therapy and remained symptom free. Case 2 is a 71-year-old female with bilateral temporo-occipital infarcts due to RCVS, presented with refractory headache and persistent vasospasm on transcranial Doppler (TCD), despite aggressive treatment with CCBs. She experienced dramatic relief of symptoms with intravenous magnesium and resolution of vasospasm on TCD. Magnesium may be beneficial for the treatment of refractory headaches in patients with RCVS. Future studies are needed to determine whether it should be considered as a first-line agent.